EKSPLORASI MINAT BELAJAR SISWA DALAM MATA PELAJARAN SENI TARI DI SD TAMAN MUDA IBU PAWIYATAN YOGYAKARTA - Poppy Indriyanti; Dyan Indah Purnama Sari (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
This study uses a qualitative method. To collect data the researcher used interview techniques, direct field observation, documentation and questionnaires. Data were analyzed using Miles and Huberman methods, namely data reduction, display data, and verifying. While testing the validity of the data include credibility test, transferability testing, dependentbility testing and konfirmability testing. The results showed that at Taman Muda Ibu Pawiyatan Yogyakarta Primary School (1). Student interest in learning dance is supported on a variety of things: the situation of students who are already generally follow arts activities outside school, dance lessons is an intrakulikuler lesson, the learning process is being held at the open room gives a very good effect. (2). How teachers implement instructional dance is the main thing in student interest in learning dance, in addition to teachers provide interesting material for study by students, teachers also use the â€œAmongâ€ systems wich engage students to learn, with the fun atmosphere. (3) Constraints faced by teachers in dance learning in this case the medium of teaching such as audio media are not yet using the digital system. Location in teaching and learning of the dance lessons impact on the level of the students concentration. Selection of appropriate materials become an obstacle in the classroom because this is an inclusive school.Keywords : interest in learning, lessons, dance, Primary School